Microvascular Changes in Macular Area After Phacoemulsification and Its Influencing Factors Assessed by Optical Coherence Tomography Angiography - Liu J; Liu Q; Yu H; Xia Y; Zhang H; Geng C; Dong L (Dove Medical Press, 2021)
Jun Liu, Qiang Liu, Hua Yu, Ye Xia, Hui Zhang, Chao Geng, Lihong Dong Department of Ophthalmology, Chaohu Hospital of Anhui Medical University, Hefei, 238000, Anhui, People’s Republic of ChinaCorrespondence: Lihong DongDepartment of Ophthalmology, Chaohu Hospital of Anhui Medical University, Hefei, 238000, Anhui, People’s Republic of ChinaTel +86-551-82324267Email dlhyp6583@sina.comObjective: To investigate macular vascular changes and underlying influencing factors using optical coherence tomography angiography (OCTA) after phacoemulsification in patients with cataracts.Methods: Patients diagnosed with cataracts at the First Affiliated Hospital of Anhui Medical University from March to September 2019 were included. The macular retinal thickness, the microvascular density in the foveal, parafoveal, and perifoveal area, and the area of the foveal avascular zone (FAZ) were measured using OCTA at baseline, 1-week, 1-month, and 3-month post-operation.Results: Forty-seven cataract patients (58 eyes) were eligible for this study. Compared with baseline thickness, the foveal, parafoveal, and perifoveal thicknesses, particularly in the inner retina, significantly increased at 1- and 3-month post-operation (P< 0.05). There was a nonsignificant difference in the microvascular density of the foveal and perifoveal areas at 1-week, 1-month, and 3-month post-operation (P> 0.05). At 1-month post-operation, the deep vessel density at the perifovea significantly increased (P< 0.05). The FAZ area significantly diminished at 1- and 3-month post-operation compared with the baseline data (P< 0.05).Conclusion: Phacoemulsification offers a satisfactory efficacy response, with an increased macular thickness, reduced FAZ area, and nonsignificant changes in the microvascular density at the perifovea after surgery.Keywords: cataracts, phacoemulsification, optical coherence tomography, macular thickness, microvascular density